2019
DOI: 10.1002/app.48041
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of PBTCA‐modified hyperbranched polyether corrosion and scale inhibitors

Abstract: In this study, hyperbranched polyether (HBP) with terminal hydroxyl was synthesized from tetrahydrofuran and glycidol by cationic open-loop polymerization and then modified by 2-phosphono-butane-1,2,4-tricarboxylic acid to introduce carboxyl and phosphorus to improve corrosion and scale inhibition. The structure of the products (HBPs) was determined by FTIR and 1 H-NMR. The scale inhibition efficiency (E) of calcium carbonate and calcium sulfate reached 99.74 and 97.10% at a concentration of 20 mg/L. X-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Recently, our group has developed a new class of modified aliphatic polycarbonates (PCA–COOH and PCA–PO 3 H 2 –COOH) as environmentally friendly oilfield SIs for carbonate and sulfate scales (Figure ). Also, Wang et al have synthesized a series of 2-phosphono-butane-1,2,4-tricarboxylic acid (PBTCA)-modified hyperbranched polyethers as biodegradable corrosion and scale inhibitors . Furthermore, Liu et al have reported a polyether copolymer as an environmentally friendly scale and corrosion inhibitor …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group has developed a new class of modified aliphatic polycarbonates (PCA–COOH and PCA–PO 3 H 2 –COOH) as environmentally friendly oilfield SIs for carbonate and sulfate scales (Figure ). Also, Wang et al have synthesized a series of 2-phosphono-butane-1,2,4-tricarboxylic acid (PBTCA)-modified hyperbranched polyethers as biodegradable corrosion and scale inhibitors . Furthermore, Liu et al have reported a polyether copolymer as an environmentally friendly scale and corrosion inhibitor …”
Section: Introductionmentioning
confidence: 99%
“…16 Also, Wang et al have synthesized a series of 2-phosphono-butane-1,2,4tricarboxylic acid (PBTCA)-modified hyperbranched polyethers as biodegradable corrosion and scale inhibitors. 17 Furthermore, Liu et al have reported a polyether copolymer as an environmentally friendly scale and corrosion inhibitor. 18 Polyethers are polymers that contain the C−O−C linkage, as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…According to the thermodynamic principle, lower E corr means a greater corrosion tendency. In terms of corrosion kinetics, the larger the I corr , the faster the corrosion reaction 21 …”
Section: Resultsmentioning
confidence: 99%
“…In terms of corrosion kinetics, the larger the I corr , the faster the corrosion reaction. 21 As shown in Figure 13 and Table 6, the cathodic polarization curves of the three test samples are parallel to each other, so it can be known that the corrosion resistance of the tested samples is mainly controlled by anode. Since there are two passivation regions in the polarization curve, 22 it can be inferred that the sample has a certain degree of selfrepair, 23 which can further play the role of corrosion inhibition.…”
Section: Electrochemical Measurementsmentioning
confidence: 97%
“…5 in high-temperature, high-hardness, and high-alkali environments. 17,18 Therefore, in this paper, hydroxypropyl acrylate (HPA) was modified by the PBTCA molecule and then polymerized with allyl polyethoxyammonium sulfonate (APES). The product (AA−APES−HPAY) has a carboxyl group, sulfonic acid group, and ether bonds as well as a low phosphorus content.…”
Section: Introductionmentioning
confidence: 99%